Exploration of the Vaginal and Gut Microbiome in African American Women by Body Mass Index, Class of Obesity, and Gestational Weight Gain: A Pilot Study - Faucher, Mary Ann; Greathouse, Kristen Leigh; Hastings-Tolsma, Marie; Padgett, Robert Noah; Sakovich, Kimberly; Choudhury, Ankan; Sheikh, Aadil; Ajami, Nadim J.; Petrosino, Joseph F. (American Journal of Perinatology, 2019)
Objective This study determines the differences in the distal gut and vaginal microbiome in African American (AA) women by prepregnancy body mass index and gestational weight gain (GWG) comparing women with and without obesity and by obesity class.Study Design We prospectively sampled the vaginal and distal gut microbiome in pregnant AA women at two time points during pregnancy. Samples were analyzed using high-throughput sequencing of the V4 region of the 16S ribosomal ribonucleic acid gene.Results Distinct differences in vaginal and distal gut α-diversity were observed at time point 1 between women with and without obesity by total GWG. Significant differences in distal gut β-diversity were also found at time point 1 in obese women by GWG. Within the Bacteroides genus, a significant association was observed by total GWG among obese women which was absent in nonobese women. Women with class III obesity who experienced low GWG had the lowest abundance of distal gut Bacteroides and appreciably higher relative abundance of a consortia of vaginal taxa including Atopobium, Gardnerella, Prevotella, and Sneathia.Conclusion These results contribute new evidence showing that GWG in combination with obesity and obesity class is associated with an altered distal gut and vaginal composition early in pregnancy among AA women.
Keywords: gestational weight gain; obesity; obesity class; microbiome; African American; pregnancy